COVID-19 impact on Facebook-based social commerce in Bangladesh - Samsul Alam; Md. Minhajur Rahman (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Popular social media Facebook-oriented social commerce (S-commerce), commonly known as Facebook commerce (F-commerce) has progressed towards a bevy business in Bangladesh. Many young people, especially at the age of 20-28, are now in this industry. The pandemic situation due to coronavirus disease 2019 (COVID-19) forces people to buy more from the online market because of the safety issue. People are getting more interested in the new trend of buying from an online store. The current study aims to explore the impact of COVID-19 on F-commerce, particularly in Bangladesh. It uses the non-probability purposive sampling method and collects 181 usable responses through an online questionnaire. A research model is developed following the social commerce acceptance model (SCAM), and structural equation model partial least square (SEM-PLS) using SmartPLS 3.0 is applied to find out and justify the result. Likert five-point scale for determining the independent variables, including COVID-19 awareness (CA), consumer behavior (CB), and purchase intention (PI), is used. The study result confirms that these three variables have a positive impact on F-commerce. The survey covers other measurable items that indicate some assumptions, which reflect F-commerce consumers’ behavior. The researchers recommend that F-commerce businesspeople must emphasize on mitigating trust issues and provide enhanced home delivery service.